Gradual pressure-induced enhancement of magnon excitations in CeCoSi - Nikitin, S.E.; Franco, D.G.; Kwon, J.; Bewley, R.; Podlesnyak, A.; Hoser, A.; Koza, M.M.; Geibel, C.; Stockert, O. (American Physical Society, 2020)
Fil: Franco, D.G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina; Max Planck Institute for Chemical Physics of Solids; Alemania